Chemical and mechanical stability of an ion-exchanged lithium disilicate glass in artificial saliva. (January 2023) - Li, X.C.; Chen, Z.X.; Li, D.; Liu, W.Z.; Meng, M.
Abstract: Multi-component lithium disilicate (LD) glasses were ion-exchanged in a pure or mixed nitrate salt bath. The surface morphologies, mechanical properties, chemical stability and ion leaching of ion-exchanged LD glasses before and after storage in artificial saliva for 21 days were investigated. It can be found that chemical stability of ion-exchanged LD glass was temperature-dependent. The residual compressive stress induced by ion-exchange increased the chemical potential of alkali ions in glass, and the ion-exchanged LD glass, especially 235 °C/64 h group, chemical stability in artificial saliva for 21 days were deteriorated. Back-exchange treatment could relax the stress on the outermost layer of the ion-exchanged LD glass without deteriorating its strengthening effect, and back-exchanged LD glass presented good chemical and mechanical stability in artificial saliva. The results might help to enhance the service stability of ion-exchanged LD glass-ceramics in the oral condition. Highlights: Chemical and mechanical stability of ion-exchanged LD glass was obviously degraded after storage in artificial saliva. Chemical stability is closely related to residual stress or ion-exchange temperature. Back-exchanged LD glass shows good chemical stability and maintaining the strengthening effect.